Undergraduate distance learners' sense of mattering at a public higher learning institution / Nur Maizura Lin - Lin, Nur Maizura (2023)
The inception of distance learning in Malaysia has brought about a significant impact on the Malaysian higher education landscape, especially among working adult learners. Adult learners reap the many benefits of distance education, nevertheless, they also face innumerable challenges. To address the overwhelming number of challenges that distance learners face, the concept of Mattering, established by Rosenberg and McCullough, and later on introduced in higher learning institutions by Schlossberg as the Theory of Mattering and Marginality is revisited. Mattering is defined as the feeling of being cared for or mattered to by another person (individual mattering) or a group of people (societal mattering). Schlossberg believed that feeling that one matters can positively affect an individual. The Theory of Mattering and Marginality consisted of five constructs, and they include awareness, importance, egoextension, reliance, and appreciation, and to measure these constructs at higher learning institutions among adult learners, Schlossberg, LaSalle, and Golec came up with The Mattering Scales for Adult Students in Higher Education (MHE). The Theoretical Framework of this study was based on the Theory of Mattering and Marginality. In view of the issues faced by distance learners, five research objectives were developed and they investigated English language distance learners' experience of mattering with regard to their peers, faculty members, administrative staff, advisors, or mentors as well as the university acknowledging them as learners holding multiple roles. The five aforementioned areas reflected the five dimensions in The Mattering Scales for Adult Students in Higher Education (MHE) survey. This mixedmethods study consisted of both qualitative and quantitative parts. Online interviews were carried out and MHE surveys were distributed for the purpose of data collection. Johnny Saldańa’s Thematic Analysis and The Statistical Package for the Social Science (SPSS) were used to analyze data from both studies. Findings from both methods revealed that in general the distance learners felt that they matter to all five dimensions (peers, lecturers, academic advisors/ mentors, administrative staff and as learners holding multiple roles). This study has made contributions from the aspects of theoretical, and methodological implications. Key directions for future research were proposed at the end of the study.